Application of Electronic and Electrical Industry in the Field of New Energy - Zheng, Boyuan (International Journal of Electric Power and Energy Studies, 2026)
This paper focuses on the application of the electronic and electrical industry in the field of new energy, and comprehensively analyzes its key role in the development of the new energy industry. By describing the current development status of the new energy industry, this paper introduces in detail the application of the electronic and electrical industry in new energy power generation systems such as solar energy, wind energy, and hydropower, as well as battery energy storage, power transmission and distribution. This paper analyzes the technological innovation and efficiency improvement brought by electronic and electrical technology to the field of new energy. It aims to reveal the important significance of the deep integration of the electronic and electrical industry with the field of new energy, provide theoretical reference and practical guidance for the development of related industries, and promote the development of the new energy industry in an efficient and sustainable direction.